UNIVERSITY BRAND AS A COMPONENT OF THE STRATEGY FOR PROMOTING EDUCATIONAL SERVICES IN THE MARKET - Tkachov , М.; Zhehus , О.; Husakovska , Т. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article explores the university brand as a crucial element in the strategy for promoting educational services in the market. The authors analyse the key factors that influence the image and reputation of higher education institutions and their effects on the university's competitiveness amid globalisation and the digitalisation of the educational landscape. The significance of branding is highlighted, especially in attracting applicants, students, faculty, partners, and investors. The article places particular emphasis on strategic approaches to developing a university's brand, including positioning, differentiation, and communication tools that enhance brand recognition. It also reviews successful cases from both domestic and international universities that have effectively implemented marketing strategies and digital technologies to strengthen their brands. Recommendations for optimising the marketing of educational services through social media, content marketing, collaboration with graduates, and the application of modern public relations tools are provided. The development of a university’s brand within the educational and market environment should consider its unique characteristics, as well as market and socio-economic conditions. This development should focus on increasing the role of the scientific and pedagogical staff of the university, its successful graduates, formed educational services and, to a certain extent, the emotional image of the higher educational institution. These elements create the necessary foundations for improving the university's competitive position within the targeted educational market. This approach considers the diverse profiles of the university brand's consumers and enhances its perception in both the labour market and the educational services sector. The findings of this study may be valuable for university leaders, marketing professionals, educational analysts, and anyone interested in advancing higher education.